1999
DOI: 10.1116/1.590993
|View full text |Cite
|
Sign up to set email alerts
|

Outlook for 157 nm resist design

Abstract: We have measured the transparencies of a number of candidate resist materials for 157 nm, with an emphasis on determining which chemical platforms would allow resists to be used at maximum thicknesses while meeting requirements for optical density. Although ideal imaging is usually obtained at an optical density between 0.1 and 0.3 and values in excess of 0.5 can often result in nonvertical wall profiles, we chose to arbitrarily choose 0.4 as the maximum tolerable optical density. Using this analysis, our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 12 publications
2
34
0
1
Order By: Relevance
“…The value of PL lifetime, t ¼ 11:5 ms; at room temperature is almost the same as that of spinel crystals (Cr doped MgAl 2 O 4 ) [4]. PL lifetime from CaAl 2 O 4 : Eu, Dy specimens calculated from the decay curves in Fig.…”
Section: Article In Pressmentioning
confidence: 93%
See 1 more Smart Citation
“…The value of PL lifetime, t ¼ 11:5 ms; at room temperature is almost the same as that of spinel crystals (Cr doped MgAl 2 O 4 ) [4]. PL lifetime from CaAl 2 O 4 : Eu, Dy specimens calculated from the decay curves in Fig.…”
Section: Article In Pressmentioning
confidence: 93%
“…Measuring temperature based on the rate of photoluminescence (PL) decay is a potentially useful technique, because it enables temperature measurement without electro-magnetic influences [1][2][3][4][5][6][7]. In the fiber-optic thermometer system, the phosphors used for a sensor head are responsible for the accuracy and the sensitivity of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Two classes of polymers with low absorbance at 157 nm were identified: certain fluoropolymers and polysiloxanes [7]. In particular, Teflon 1 AF, an amorphous copolymer of tetrafluoroethylene (TFE) and perfluoro(2,2-dimethyldioxole), was found to have an absorbance of about 0.7 mm À1 at 157 nm.…”
Section: Role Of Fluoropolymersmentioning
confidence: 99%
“…Although the maximum tolerable absorbance of a resist binder polymer is still under discussion, most agree that it must be under about 2 mm À1 and preferably under 1 mm À1 . Studies showed that known resists are far too absorbing for use at 157 nm at a reasonable film thickness (Table 1) [6,7]. Styrenic and (meth)acrylate polymers are above 6 mm À1 , orders of magnitude higher than the goal value.…”
Section: Photoresist Technologymentioning
confidence: 99%
“…The fiberoptic thermometer based on fluorescence lifetime is one of the most promising techniques for the temperature measurement in the extraordinary environments [1][2][3][4][5][6][7][8][9]. In this thermometer system, the phosphors used in the sensor head are responsible for the accuracy and sensitivity of the measurements.…”
Section: Introductionmentioning
confidence: 99%